About the question of the direct action of the norms of the Constitution of the Republic of Kazakhstan (Халықаралық қатынастар және халықаралық құқық сериясы, 2017)
The relevance of the research question of the direct action of the Basic Law is connected with the fact that it is a legal act which should be guided by the requirements of all the organs of the state, organizations, public associations and citizens. At the same time the principle of direct action is formally declared and it is not regulated in a procedural terms nor in the Constitution of the Republic of Kazakhstan nor in the current legislation. This suggests the need to develop the concept of direct action of the Constitution of the Republic of Kazakhstan, which would be adequate to the needs of the present stage of the constitutional and legal development of society and the state and fully meet their needs. This concept would become an integral part of the theory of the implementation of the Constitution, which could cover the entire social mechanism of its action in society and state.